2012
DOI: 10.1026/1616-3443/a000153
|View full text |Cite
|
Sign up to set email alerts
|

Ein Gruppenbehandlungsprogramm zur Bewältigung von schweren Brandverletzungen

Abstract: Theoretischer Hintergrund: Schwere Verbrennungen verursachen häufig bleibende körperliche Einschränkungen und Entstellungen. Viele Betroffene fühlen sich beim Bewältigungsprozess der Unfallfolgen überfordert. Das deutschlandweit erste verhaltenstherapeutische Gruppenbehandlungsprogramm speziell für Brandverletzte wurde entwickelt, um Betroffene bei der Bewältigung der längerfristigen Folgen des Unfalls und der Rückkehr in den Alltag zu unterstützen. Fragestellung: Ziel der Arbeit ist die Beschreibung des Progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…Quality of life was substantially lower in the IG and the TAU group compared to the nonclinical control sample, indicated by lower WHOQOL scores (t(83-123) = 4.16-5.61, all p < .05). In accordance with other studies of burn patients [3,4], the present burn sample reported high levels of psychosocial resources: the IG as well as the TAU group showed higher levels of optimism (LOT; t(84-124) = 11.14-16.5, all p < .05) and social support (F-SozU-K-14, t(84-124) = 3.19-4.01, all p < .05) compared to nonclinical populations.…”
Section: Participantssupporting
confidence: 93%
See 3 more Smart Citations
“…Quality of life was substantially lower in the IG and the TAU group compared to the nonclinical control sample, indicated by lower WHOQOL scores (t(83-123) = 4.16-5.61, all p < .05). In accordance with other studies of burn patients [3,4], the present burn sample reported high levels of psychosocial resources: the IG as well as the TAU group showed higher levels of optimism (LOT; t(84-124) = 11.14-16.5, all p < .05) and social support (F-SozU-K-14, t(84-124) = 3.19-4.01, all p < .05) compared to nonclinical populations.…”
Section: Participantssupporting
confidence: 93%
“…As previously reported, the overall patient satisfaction with the group treatment was high [3]. This is particularly noteworthy because in another study nearly one fourth of burn patients seeking help because of physical or psychological problems reported to be dissatisfied with the received services [21].…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations